Respuesta de tres híbridos de pepino cucumis sativus l. a la fertilización orgánica en la granja experimental Santa Inés - Ordóñez León, Ruth Aracely (2008)
During the months of September to December of the year 2007, was evaluated the hybrid Answer of three of cucumber (Cucumis sativus L.) to the organic fertilization. The experiment tes, was made in the lands of the experimental grange Santa Inés in the College of Agricultural Sciences of the Technical University of Machala, having as objectives: 1. to evaluate the hybrid answer of three from cucumber to the organic fertilization in the experimental grange Santa Inés; 2. to establish that material evaluated presents the best yield in the cucumber production and 3. make an economic analysis of the treatments; the different doses of organic fertilizer to him divided in two parts, and the first one was applied, in the moment of the transplant and the other one to the fifteen days after the sowing. Them analyses of variance of the design divided parcels, demonstrated that alone the variance of hybrid was significant with a level significance of 1%, in the variables, number of fruits, weight of fruits, longitude of fruits and yield for parcel and hectare. Conjuncion with the results obtained the best hybrid it was Dasher II with a production average of 31,99 - 27,89 t/h, in the context agricultural ecological of the experiment tes the yields more below corresponded those of the hybrid Blitz with their four levels of fertility include the witness with values average of 20,03 - 15,87 t/h, from the economic point of view the hybrid Dasher II and Thunder with their respective levels of fertility threw the values but high in the profitability and benefit cost, with values averages between 3,35 and 2,6 dollars. Obtained the results you reached the conclusion that the productivities more high they were given with the hybrid Dasher II and Thunder and that the same ones are not influenced with the levels of fertility, but if for their genetic characters.